Catechin-driven dual metabolic modulation enhances docosahexaenoic acid biosynthesis and oxidative stability in Schizochytrium sp - Chengxi Zhang; Zifan Zhang; Yuxuan Chen; Yingfeng Li; Guang Yang; Xiaoman Sun; Wang Ma (Bioresource Technology, 2027)

Hydrophilic PAMAM dendrimer grafted Janus membrane for oil-water emulsion separation - Yunqi Chen; Xiang Wang; Haoyuan Sun; Xinqiang Wang; Baihu Dong; Chaogang Fan; Yingfeng Tu; Shaohui Lin; Qinmin Pan; Xianshe Feng; Flora T.T. Ng (Journal of Environmental Chemical Engineering, 2026)

Mg hydrogen generator based intelligent responsive stent for in situ therapy of reflux esophagitis - Guokai Zeng; Junjie Liang; Yuxuan Zhang; Guofeng Zeng; Xiaoying Li; Qiansha Luo; Bingjun Wu; Yuxin Tang; Jiazheng Chen; Shuhan Zhou; Fang Qin; Qi He; et al. (Chemical Engineering Journal, 2026)

Separation of vanadium and molybdenum from a sulfuric acid leachate - Bingxu Chen; Chunliu Li; Huaijiang Wang; Ruishu Wang; Yingfeng Cuan; Haojie Meng; Bingwu Chu (Hydrometallurgy, 2026)

Regulation of air-sea CO2 flux and aragonite saturation state in coral reef ecosystems along the eastern coast of Hainan Island, China - Wei Yang; Zijia Zheng; Peiqiang Zhuang; Jianhang Zhang; Wei Deng; Shengyong Li; Yanmei Liu; Ming He; Yingfeng Chen; Bingbing Yu; Xinxin Xu; Xinxing Li; et al. (Marine Pollution Bulletin, 2026)

Preparation–structure–function relationships governing syneresis behavior in alkali-induced konjac glucomannan gel - Xiaoxuan Chen; Yingfeng Zhang; Chunan Sun; Guohua Zhao; Yun Zhou (Food Chemistry, 2025)

Tanshinone IIA ameliorates pancreatic injury in type 2 diabetic mice by modulating inflammation and endoplasmic reticulum stress via the IL-6/JAK2/STAT3 pathway - Yingfeng Li; Desheng Wang; Yuhang Liu; Chenyang Liu; Meixi Chen; Jingqi Li; Zunqiu Wu; Ning Wu (Functional & Integrative Genomics, 2025)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

Carboxymethyl chitosan and poly-γ-glutamic acid-based gastroretentive sponge with high swelling and mechanical stability for targeted eradication of Helicobacter pylori - Xinyuan Zhang; Pei Xie; Yongkang Lai; Jiulong Zhao; Qiuping Gu; Yingfeng Wei; Zheng Chen; Liang Zhang; Shige Wang; Hongxin Sun; Chunping Zhu (Carbohydrate Polymers, 2025)

Balance between strength and toughness for fully bio-based composites achieved by oriented design of filler - Kang Chen; Ruixia Liu; Ce Sun; Dingyuan Zheng; Yuanyuan Miao; Yingfeng Zuo; Haiyan Tan; Yanhua Zhang (Chemical Engineering Journal, 2025)

Seismic Prediction of Shallow Unconsolidated Sand in Deepwater Areas - Jiale Chen; Yingfeng Xie; Tong Wang; Haoyi Zhou; Zhen Zhang; Yonghang Li; Shi Zhang; Wei Deng (Journal of Marine Science and Engineering, 2025)
Recently, shallow gas fields and hydrate-bearing sand in the deepwater area of the northern South China Sea have been successively discovered, and the accurate prediction of shallow sands is an important foundation. However, most of the current prediction methods are mainly for deep oil and gas reservoirs. Compared with those reservoirs with high degree of consolidation, shallow sandy reservoirs are loose and unconsolidated, whose geophysical characteristics are not well understood. This paper analyzes the logging data of shallow sandy reservoirs recovered in the South China Sea recently, which show that the sand content has a significant influence on Young’s modulus and Poisson’s ratio of the sediments. Therefore, this paper firstly constructs a new petrophysical model of unconsolidated strata targeting sandy content and qualitatively links the mineral composition and the elastic parameters of the shallow marine sediments and defines a new indicator for sandy content: the modified brittleness index (MBI). The effectiveness of MBI in predicting sandy content is then verified by measured well data. Based on pre-stack seismic inversion, the MBI is then inverted, which will identify the sandy deposits. The method proposed provides technical support for the subsequent shallow gas and hydrate exploration in the South China Sea.

Spatio-Temporal Dynamics of Particulate Organic Carbon and Its Response to Climate Change: Evidence of the East China Sea from 2003 to 2022 - Zhenghan Liu; Yingfeng Chen; Xiaofeng Lin; Wei Yang (Journal of Marine Science and Engineering, 2025)
Particulate organic carbon (POC) plays a crucial role in oceanic climate change. However, existing research is limited by several factors, including the scarcity of long-term data, extensive datasets, and a comprehensive understanding of POC dynamics. This study utilizes monthly average POC remote sensing data from the MODIS/AQUA satellite to analyze the spatiotemporal variations of POC in the East China Sea from 2003 to 2022. Employing correlation analysis, spatial autocorrelation models, and the Geodetector model, we explore responses to key influencing factors such as climatic elements. The results indicate that POC concentrations are higher in the western nearshore areas and lower in the eastern offshore regions of the East China Sea (ECS). Additionally, concentrations are observed to be lower in southern regions compared to northern ones. From 2003 to 2022, POC concentrations exhibited a fluctuating downward trend with an average annual concentration of 121.05 ± 4.57 mg/m3. Seasonally, monthly average POC concentrations ranged from 105.48 mg/m3 to 158.36 mg/m3; notably higher concentrations were recorded during spring while summer showed comparatively lower levels. Specifically, POC concentrations peaked in April before rapidly declining from May to June—reaching a minimum—and then gradually increasing again from June through December. Correlation analysis revealed significant influences on POC levels by particulate inorganic carbon (PIC), sea surface temperature (SST), chlorophyll (Chl), and photosynthetically active radiation (PAR). The Geodetector model further elucidated that these factors vary in their impact: Chl was identified as having the strongest influence (q = 0.84), followed by PIC (q = 0.75) and SST (q = 0.64) as primary influencing factors; PAR was recognized as a secondary factor with q = 0.30. This study provides new insights into marine carbon cycling dynamics within the context of climate change.

Evaluating the impacts of drilling and extraction activities on the marine carbonate system in the natural gas fields of Beibu Gulf, Northern South China Sea - Minxia Zhang; Wei Yang; Jianhang Zhang; Chuqian Lu; Yingxu Wu; Peiqiang Zhuang; Yanmei Liu; Shasha Qi; Xing Chen; Wei Deng; Zijia Zheng; Ming He; et al. (Marine Environmental Research, 2025)

Large-scale interviews and plot-based data reveal declining yields of the prized matsutake mushrooms in the major producing areas of China - Yingfeng Bi; Bin Liu; Guangli Chen; Ti Bu; Pengwan Zhang; Qinghong Zhou; Liqin Mu; Yao Fu; Yinxian Shi; Xuefei Yang; Deli Zhai (Journal of Environmental Management, 2025)

Micromotors assisted in vivo dopamine polymerization for anti-tumor therapy - Dailing Du; Ye Feng; Miaomiao Ding; Jinghui Rong; Bin Chen; Chao Gao; Tingting Jiang; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2025)

Exploring the Dynamic Evolution of Shallow and Deep Coal Nanopore Structures Under Acidic Fracturing Fluids Using Synchrotron Radiation Small-Angle X-Ray Scattering - Yingfeng Sun; Shuaipeng Zhu; Hui Wang; Yixin Zhao; Fei Xie; Ping Chen; Changjiang Ji; Zhaoying Chen; Qifei Wang (Natural Resources Research, 2025)

Logic combination and diagnostic rule-based method for consistency assessment and its application to cross-sensor calibrated nighttime light image products - Zihao Zheng; Qiming Zheng; Zhifeng Wu; Zheng Cao; Hong Zhu; Yingbiao Chen; Benyan Jiang; Yingfeng Guo; Dong Xu; Francesco Marinello (Remote Sensing of Environment, 2025)

VNI-Net: Vector neurons-based rotation-invariant descriptor for LiDAR place recognition - Gengxuan Tian; Junqiao Zhao; Yingfeng Cai; Fenglin Zhang; Xufei Wang; Chen Ye; Sisi Zlatanova; Tiantian Feng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Toward the bioactive potential of myricitrin in food production: state-of-the-art green extraction and trends in biosynthesis - Yaqian Geng; Yingfeng Xie; Wei Li; Yao Mou; Fang Chen; Jianbo Xiao; Xiaojun Liao; Xiaosong Hu; Junfu Ji; Lingjun Ma (Critical Reviews in Food Science and Nutrition, 2024)

Helical hydrogel micromotors for delivery of neural stem cells and restoration of neural connectivity - Suyi Liu; Bin Chen; Ye Feng; Chao Gao; Dailing Du; Tingting Jiang; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2024)

A catastrophic rainfall-induced high landslide, occurred on December 4, 2020, in the Qingliucun mountainous area of Southwest China - Demin Xue; Cong Dai; Yingfeng Wu; Kai Chen; Jibing Tang; Shuai Zhang (Landslides, 2023)

The temporal and spatial variation of chlorophyll a concentration in the China Seas and its impact on marine fisheries - Kunlong Zhang; Xunbo Zhao; Jing Xue; Danqi Mo; Dongyu Zhang; Zhongyong Xiao; Wei Yang; Yingxu Wu; Yingfeng Chen (Frontiers in Marine Science, 2023)
Marine chlorophyll a is a key molecule for photosynthesis of marine plants and some plankton, which is important in marine ecosystems. This study utilized the chlorophyll a concentration data product observed by the MODIS sensor (MODerate resolution Imaging Spectroradiometer) to construct a long-term sequence of chlorophyll a concentration dataset by processing the raw data. Based on this, the multi-time-scale chlorophyll a concentration data was synthesized, and it was used to analyze the spatial and temporal variation characteristics of chlorophyll a concentration in China Seas. In addition, several oceanographic variables, including sea surface temperature, nutrients (phosphate, nitrate, silicate), partial pressure of seawater carbon dioxide, net primary productivity of the ocean, physical dynamics of seawater processes (mixed layer), were analyzed to ascertain their potential influence on chlorophyll a concentration. Finally, we analyzed the effects of changes in chlorophyll a concentration on marine fisheries. The result showed that: The average value of chlorophyll a concentration in China Seas from 2002 to 2022 was 0.874 mg/m 3 , with the highest concentration observed in the Bohai Sea area (4.547 mg/m 3 ) and the lowest in the South China Sea area (0.288 mg/m 3 ). The spatial variation of chlorophyll a concentration revealed an overall decrease of 0.0095 mg/m 3 in China Seas from 2002 to 2022. From the perspective of time changes, the concentration of chlorophyll a in China’s Bohai Sea area showed a downward trend from 2002 to 2022, while the Yellow Sea area showed an upward trend. The concentration remained relatively stable in the East China Sea area, whereas a significant declining trend was observed in the South China Sea area. The relationship between temperature and chlorophyll a concentration was non-linear, and chlorophyll a concentration showed some fluctuation or threshold effect with the change of seawater temperature. The three nutrient salts studied have a promoting effect on chlorophyll a, among which phosphate has the most obvious promoting effect on chlorophyll a. Chlorophyll a was negatively correlated with pCO 2 and positively correlated with ocean net primary productivity. Seasonal changes in the mixed layer had a significant effect on changes in the upper marine nutrients, which in turn affected changes in chlorophyll a concentration. Six of the eight types of algae studied show a trend toward deeper sea depths, which may have implications for the food availability of marine fish at different levels and pose new challenges for marine fisheries development.

Light-driven micromotor swarm induced in-situ polymerization and synergistic photothermal therapy - Zeqi Li; Shaoming Fu; Huaan Li; Bin Chen; Dazhi Xie; Dongmei Fu; Ye Feng; Chao Gao; Suyi Liu; Daniela A. Wilson; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2023)

New insights into enhanced electrochemical advanced oxidation mechanism of B-doped graphene aerogel: Experiments, molecular dynamics simulations and DFT - Wenwen Gu; Mingwang Yang; Zhuang Chen; Ting Cao; Yimei Zhang; Yingfeng Li; Ranran Zhang (Journal of Hazardous Materials, 2023)

Retraction Note to: Detection of oasis soil composition and analysis of environmental parameters based on hyperspectral image and GIS - Yingfeng Chen; Zhongyong Xiao; Guoqiang Chen; Weimin Su; Jiongfeng Chen (Arabian Journal of Geosciences, 2021)

RETRACTED ARTICLE: Detection of oasis soil composition and analysis of environmental parameters based on hyperspectral image and GIS - Yingfeng Chen; Zhongyong Xiao; Guoqiang Chen; Weimin Su; Jiongfeng Chen (Arabian Journal of Geosciences, 2021)

The spatio-temporal characteristics of aerosol optical thickness as well as the relationship with PM2.5 in Xiamen city, China - Zhongyong Xiao; Xianquan Xie; Xiaofeng Lin; Jinghan Xie; Jiongfeng Chen; Yiqiang Shi; Yingfeng Chen (Environmental Monitoring and Assessment, 2020)

Quantitative study on the fate of antibiotic emissions in China - Shuxin Chen; Jing Wang; Huajun Feng; Dongsheng Shen; Shichong He; Yingfeng Xu (Environmental Geochemistry and Health, 2020)

Experimental Investigation of Rock Drillability for Three Rock Types Under Varying Wellbore Pressure Conditions - Shuai Mao; Xiangchao Shi; Yingfeng Meng; Ping Chen; Xiao Zhuo; Louis Ngai Yuen Wong (Rock Mechanics and Rock Engineering, 2018)

DDX50 inhibits the replication of dengue virus 2 by upregulating IFN-β production - Peijun Han; Wei Ye; Xin Lv; Hongwei Ma; Daihui Weng; Yangchao Dong; Linfeng Cheng; Hesong Chen; Liang Zhang; Zhikai Xu; Yingfeng Lei; Fanglin Zhang (Archives of Virology, 2017)

Peroxisome proliferator-activated receptor γ inhibits pulmonary hypertension targeting store-operated calcium entry - Yingfeng Wang; Wenju Lu; Kai Yang; Yan Wang; Jie Zhang; Jing Jia; Xin Yun; Lichun Tian; Yuqin Chen; Qian Jiang; Bo Zhang; Xiuqing Chen; et al. (Journal of Molecular Medicine, 2015)

Thidiazuron promotes adventitious shoot regeneration from pothos (Epipremnum aureum) leaf and petiole explants - Luping Qu; Jianjn Chen; Richard J. Henny; Yingfeng Huang; Russell D. Caldwell; Cynthia A. Robinson (In Vitro Cellular & Developmental Biology - Plant, 2002)